Movement towards moral recovery value-clarification for social transformation : a trainor's manual - Ramirez, Mina M. (Manila Asian Social Institute, 1993)
Purpose: Intended to be a "source for those interested in initiating, fostering or maintaining the movement towards moral recovery."
Content/s: Moral Crisis. Moral Regeneration. Personal and national action perspectives. Moral force. Symbols and symbols creation. Value transformation. Group sessions.
Keywords: Social ethics; Social groups -- Handbooks, manuals, etc; Values; Philippines -- Moral conditions